Business model for the intervention of the Association of Skill Teachers of the National University of San Agustín for the solution to the housing problem of its associates - Delgado Lujan, Juan Carlos (2016)
The members of the  Asociación  of  Docentes  from  Derrama UNSA (ADEDUNSA) propose the construction of a housing association through the following research which will have ADEDUNSA as its axis. The actual research develops an economic business characterized as a simple financial model. Thus the association will acquire land, develop the project and formalize a partnership with the Construction Company and Bank in order to concretize the desired housing project. The architectural conceptualization involves an urban dynamic that understands an intelligent and social coexistence with the environment, respecting independence. Sustainability in architecture is our target which could become a model to be followed. Objective: Business management nowadays, in any kind of organization, must be based around the management of knowledge. The ADEDUNSA (ADEDUNSA) was conceived to further savings within its members. According to a survey conducted over 70% of the member base agree to intervene in housing, which is a matter not included within the statutes. The present article expresses the proposal of the current directive. That of formulating a business model that, within ADEDUNSA, could attend to this demand without compromising the objectives nor modifying the statutes of the institution. It implies the development of a business model and the conceptualization of a sustainable architectonic project. Objectives: The authour of this article are ADEDUNS´S nembers.The rules of the association has the main objectives generte a bag of compensation with the monthly svings that every member make and the services that jhelp the quaity of their lifes and families by a suscription of contracts with trial parties. This is made by loans, agreements for peronal buvial or families , services with companies of health, turism, transport, business activities and others. Method: The research is of the social, applied, descriptve and purposing kind. It is based on primary information sources, associates and secondary research made by institutions related to the theme at hand. The statistical method is applied for the necessary diagnosis needed for the proposed business model. Thus enables the formulation of models as explanatory tools whose purpose is to generate a theoretical proposal veritable and feasible. Results: The display of an idea to solve the housing problem of ADEDUNSA members, with the same entity performing as articulator between actors in a project of this nature and future housing associations to be established. The solution has two channels. The first one being financial economics which are addressed by the proposal of the business model as funding for the project. The second is the architectural aspect, conceptualized from the social point of view attending to the needs of members within a modern, environmental urban framework. The present work allows for shaping the whole process to be implemented to achieve its mission. Conclusion: The suggested business model and architectural proposal presented here are viable and feasible to achieve. It will depend on the actions taken by the current board of the association to follow the steps presented in model, adopting it as a plausible line of action to be improved within its development. Its structure will depend on convening the right actors, determining the appropriate roles, and achieve their willingness to intervene with their best business and professional skills. The association has the financial resources to finance the purchase of land and the development of the architectural project through individual loans. With those, the participation of a construction company and a bank to materialize the project and to fund the work to completion will be sought out.